Interplay among Work Engagement, Cynicism, and Turnover Intentions: A Structural Equation Modeling Approach (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2018)
Work engagement has produced a lot of enthusiasm and significance in the research fields predominantly in organization behavior and now a day‘s generally utilized trend for organizational consultants. The main objective of this study was to find out the mediating role of work engagement between, cynicism and turnover intentions among the employees working in public sector universities. An attempt was made to construct a model which measured the mediating effects work engagement between cynicism and turnover intentions. Demographic variables and other relevant were analyzed through SPSS V 22 and structure equation model SEM was used to find out the effects of work engagement as mediating variable was measured by AMOS V 20. Work engagement was used as mediating variable between cynicism and turnover intentions.Findings of the study provide evidence that indirect effects show negative and significant relationships exist between cynicism and work engagement and significant but negative relationship between work engagements and employee turnover intentions. On the other hand, the total and direct effects describes that cynicism are positive and significantly correlated with employee‘s turnover intentions and work engagement play mediating role. The mediating role of work engagement influence cynicism on the relationship of direct and indirect effects which further recommends that employee job dimensions can affect working atmosphere along with administrative behaviors and attitudes in various directions.